Evaluation of the adherence of municipalities and states to the Ministry of Health’s microplanning for high-quality vaccination activities and the increase in vaccination coverage in Brazil - Ana Catarina de Melo Araújo; Thales Philipe Rodrigues da Silva; Gustavo Velasquez-Melendez; Luciana Maiara Diogo Nascimento; Carla Conceição Ferraz; Fernanda Penido Matozinhos; Eder Gatti Fernandes (BMC Public Health)
Abstract Background Immunization is a significant public health achievement for the whole world, although the population’s adherence to vaccination efforts remains a concern. To address this, Brazil’s Ministry of Health introduced the concept of operational microplanning (OM) for high-quality vaccination activities (HQVA) in 2023 to ensure excellence in routine service and campaigns. OM is defined by structured interventions using assertive techniques to enhance the likelihood of covering a broader population previously unprotected from vaccine-preventable diseases. Objective To assess the adherence of states and municipalities to OM for HQVA and examine the relationship between adherence levels and increased vaccination coverage in Brazil. Methods Adopting an epidemiological approach with an ecological design, this study analyzed data on the adherence of the 27 Brazilian federative units to HQVA, as reported through the REDCap electronic form in 2023, as per an agreement with the Ministry of Health. The criteria for assessing the states’ adherence to the OM included: (1) Formation of a coordination committee for the OM for HQVA; (2) Inclusion of representatives from Primary Care in the committee; (3) Inclusion of representatives from COSEMS in the committee; (4) Regular coordination meetings between health surveillance and primary care for vaccination actions; and (5) Utilization of a management tool for decision-making and strategic planning (e.g., SWOT). Adherence levels were categorized as: 0 = High adherence (responding positively to 4 or 5 criteria); 1 = Medium adherence (3 positive responses); 2 = Low adherence (2 or fewer positive responses). For municipalities, the adherence criteria were similar, excluding the COSEMS representation and focusing on the involvement of primary care representatives. Results The findings indicated that 45.75% of municipalities achieved full adherence, implementing all the evaluated actions. Despite declaring adherence to the OM, ~ 30.68% of municipalities executed two actions, 19.27% only one, and 4.30% none. Among the states, 37.04% showed full adherence by employing all evaluated actions, with 33.33% executing four actions. States with higher adherence levels to the OM also had greater vaccination coverage (VC), particularly in 2023. Municipalities with complete adherence to the OM met the VC objectives for polio (D3), 10-valent pneumococcal (D2), and triple viral (D1) vaccines in 2023. In states with full adherence to the OM, most municipalities achieved the VC targets for all evaluated vaccines in 2023, showing statistical significance for pentavalent (D3), polio (D3), and 10-valent pneumococcal (D2) vaccines. Conclusion The findings underscore the impact of OM on improving VC in Brazil, demonstrating that its effective implementation is correlated with meeting VC targets, especially in states and municipalities that enacted all recommended actions. Municipalities engaging in all OM actions met VC objectives for crucial vaccines, highlighting the OM’s positive influence on VC. Full adherence to the OM by states correlated with a notable rise in VC averages across all analyzed vaccines. This analysis suggests that higher adherence to OM improves VC outcomes, emphasizing the role of OM in these metrics and shows that comprehensive implementation of OM improves vaccination efforts and significantly boosts VC, particularly in states fully adhering to guidelines.